Microstructure and Performances for Wear-Resistant Steel through the WAAM Technology. (26th November 2021) - Ying, Meng; Guo, Chun; Li, Yun; Kang, Tai Yu; Liu, Wu Meng; Wu, Sui Song
Abstract : This work describes the wire arc additive manufacturing (WAAM) approach used to fabricate parts from wear-resistant steel. The microstructure, crystal structures, and mechanical properties of the resulting samples were thoroughly analyzed. The wear-resistant steel parts demonstrated good forming, no internal defects, good metallurgical bonding, and excellent wear resistance. The metallographic analysis confirmed that the main phase was ferrite. The microhardness of the sample along its cross section was uniform in both horizontal and vertical directions and equals to 464.7HV0.2 and 482.4 HV0.2, respectively. The average values of tensile strength, elongation ratio, and room temperature Charpy shock were equal to 945.3 MPa, 4.3%, and 5 J, respectively.